PENGARUH MOTIVASI KERJA DAN BUDAYA ORGANISASI TERHADAP KINERJA PEWAGAI BADAN PERENCANAAN PEMBANGUNAN DAERAH (BAPPEDA) KABUPATEN KAMPAR - wahyudi Teguh; Marnis Marnis; Roesdy Rosnelly (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine the effect of work motivation and organizational culture on the performance of employees of the regional development planning agency (BAPPEDA) of Kampar district located on Jl. Lingkar Kota Bangkinang.The population in this study were 66 employees. The data collection technique used a census. then using the instrumental test, validity test and reliability test. The method of analysis used in this research is regression analysis using SPSS 23 for windowsFrom the results of the tests that have been carried out, the simultaneous regression test (f test) shows that the work motivation and organizational culture variables simultaneously have a significant effect on employee performance. And the results of the partial test (t test) show that the variable work motivation and organizational culture partially has a significant effect on employee performance. The calculation result of the coefficient of determination (R2) is 0.579, which means that the percentage effect of work motivation and organizational culture on performance is 57.9%. While the remaining 42.1% is influenced by other variables that are not included in this regression model.Keywords: employee performance, work motivation, organizational culture